Aromatase inhibitor-induced arthralgia ameliorated by Mediterranean diet and active lifestyle guided by continuous glucose monitoring: a case report and review of the literature - Wilson, Kalin L.; Grewelle, Richard E.; Gupta, Tanya; Kim, Sun H.; Katsumoto, Tamiko R. (Frontiers in Oncology, 2024)
Aromatase inhibitors (AIs) are a cornerstone adjuvant treatment of many hormone receptor-positive breast cancers, and nearly half of women taking aromatase inhibitors suffer from AI-induced arthralgia (AIA), also known as AI-associated musculoskeletal syndrome (AIMSS), for which there are limited evidence-based treatments. Pharmacologic management and complementary methods including supplements, exercise, physical therapy, yoga, acupuncture, and massage have all shown mixed results. Comprehensive diet and lifestyle strategies are understudied in AIA/AIMSS despite their disease-modifying effects across many chronic conditions. Here we report a case of a woman with stage 2 estrogen and progesterone receptor-positive invasive ductal carcinoma on adjuvant anastrozole whose AI-induced arthralgia was durably controlled through a Mediterranean plant-forward diet and daily physical activity guided by continuous glucose monitoring. We posit that diet and a lifestyle inclusive of daily physical activity constitute a low-cost, low-risk, and potentially high-reward strategy for controlling common AI-induced musculoskeletal symptoms and that more investigation in this arena, including well-designed randomized trials, is warranted.